2020
DOI: 10.1590/fst.09419
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic characterization, thermal and pH inactivation study of peroxidase and pectin methylesterase from tomato (Solanum betaceum)

Abstract: Peroxidase (PDD) and pectin methylesterase (PME) from tomato were characterized, studied thermal stability, and analyzed the synergistic effect of temperature and pH. For PDD, the optimal activity, using H 2 D 2 as substrate and ABTS +• as the donor H + , was obtained at pH 3.5, and for PME, the optimal activity using pectin as substrate was obtained at pH 7.5. On PDD, it was found that the values of K M , V m and K si for H 2 D 2 were 477.26 mM, 721.53 µM/min and 0.37 mM, respectively. On PME, the values of K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…A similar behavior of significant and rapid decline in PPO activity compared to POD activity was observed during ultraviolet treatment on TCW (Augusto, Ibarz, Garvín, & Ibarz, 2015). Complete inactivation was found at 90°C during thermal inactivation for POD extract from tomato (de los Santos et al, 2020), whereas complete inactivation was observed at 95°C for TCW.…”
Section: Resultsmentioning
confidence: 99%
“…A similar behavior of significant and rapid decline in PPO activity compared to POD activity was observed during ultraviolet treatment on TCW (Augusto, Ibarz, Garvín, & Ibarz, 2015). Complete inactivation was found at 90°C during thermal inactivation for POD extract from tomato (de los Santos et al, 2020), whereas complete inactivation was observed at 95°C for TCW.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is hypothesised that the inactivation of these two enzymatic activities of the starfruit juice followed the first‐order kinetic model. The finding obtained is in line with results reported in fruit juices, such as coconut water (Tan et al ., 2014), pomegranate (Rayan & Morsy, 2020), peach (Toralles et al ., 2005), pineapple (Lee et al ., 2009; Chakraborty et al ., 2015), tomato (Santos et al ., 2020), and wax apple (Seow et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Pectin methylesterase (PME) activity was measured by the method described by Santos et al (2020). The reaction solution contained 2 mL of 0.5% pectin solution, 0.15 mL of 0.01% bromothymol blue, 0.85 mL of water, and 400 µL of sample enzyme solution.…”
Section: Enzyme Activitiesmentioning
confidence: 99%